2020
DOI: 10.3390/cells9020359
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Nucleoprotein CST/Shelterin Complex Involved in the Telomere Maintenance and Its Association with Disease Mutations

Abstract: Telomere comprises the ends of eukaryotic linear chromosomes and is composed of G-rich (TTAGGG) tandem repeats which play an important role in maintaining genome stability, premature aging and onsets of many diseases. Majority of the telomere are replicated by conventional DNA replication, and only the last bit of the lagging strand is synthesized by telomerase (a reverse transcriptase). In addition to replication, telomere maintenance is principally carried out by two key complexes known as shelterin (TRF1, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 254 publications
0
17
0
Order By: Relevance
“…This provides one possible mechanistic understanding to telomere syndromes caused by CST mutations. Since CTC1 loss results in unregulated telomere length, fragile telomeres, and increased genomic instability, the CST cancer-associated mutations in Supplementary Table 1 may contribute to oncogenesis 12 , 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides one possible mechanistic understanding to telomere syndromes caused by CST mutations. Since CTC1 loss results in unregulated telomere length, fragile telomeres, and increased genomic instability, the CST cancer-associated mutations in Supplementary Table 1 may contribute to oncogenesis 12 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The CST complex is also critical in maintaining telomere homeostasis 11 . The human CST complex composed of CTC1, STN1, and TEN1 12 has dual roles in mediating telomere homeostasis. CST terminates the telomerase extension reaction 13 either by sequestering the telomeric overhang or via disruption of the TERT–TPP1 interaction 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the upregulation of POT1 was necessary in restoring and maintaining 3′-overhang lengths in telomerase reactivated cancers, so as to prevent DNA damage response activation and to prolong survival and proliferation of cancer cells [ 258 ]. Numerous deleterious mutations in POT1 have been identified in different human cancers [ 259 ], many of which exist in the DNA-binding domain and disrupt POT1′s binding to 3′-overhangs, promoting telomere elongation and chromosomal instability. A handful of mutations occur in the TPP1-binding domain.…”
Section: The Shelterin Complexmentioning
confidence: 99%
“…Hence, premature shortening of telomere repeats leads to premature cell senescence [62]. Regarding the variant molecular interactions of the mutant TIN2 protein with its natural ligands, the readers are referred to the respective literature [63][64][65]. It is still under debate whether the extent of telomere shortening is generally associated with the severity of symptoms [66,67].…”
Section: Genetic Background and Telomere Biologymentioning
confidence: 99%